A method for preparing titanium-based brazing alloy powder

By using magnesium powder additives and microwave sintering technology in the preparation of titanium-based solder powder, the problems of uneven composition, serious pollution and high cost in the preparation of existing solder powders are solved, and high purity and low-cost titanium-based solder powders are achieved, which improves brazing quality and process performance.

CN116000302BActive Publication Date: 2025-04-11CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211635800.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-11
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The existing titanium-based brazing powder preparation methods have problems such as uneven composition, poor fluidity, serious pollution and high production costs, making it difficult to ensure brazing quality and economicality.

Method used

The method of microwave sintering → hydrogenation → crushing → screening under an inert protective atmosphere is adopted. Through the addition of magnesium powder and microwave sintering technology, uniform dissolution and sintering of elements such as titanium, zirconium, copper, nickel is achieved, avoiding the contamination of crucible materials and reducing the complexity of equipment and processes.

Benefits of technology

The low-cost preparation of high-purity titanium-based brazing powder is achieved, which ensures component uniformity and fluidity, reduces production costs, and improves brazing quality and process performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004007219050000061
    Figure BDA0004007219050000061
Patent Text Reader

Abstract

The present invention provides a method for preparing titanium-based solder alloy powder. The method uses raw material powders such as single substance powders of titanium and alloy elements (or hydrogenated powders, or pre-alloyed powders) and magnesium powder as raw materials. The steps of powder preparation include: powder mixing → pressing → microwave sintering under an inert protective atmosphere → hydrogenation → crushing → screening. The advantages of this method are that the obtained titanium-based solder powder has high purity, high fine powder acquisition rate and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing titanium-based solder alloy powder, which is suitable for low-cost preparation of high-purity titanium-based solder alloy powder. Background Art

[0002] Titanium alloy is an indispensable structural material in the field of aerospace, and is widely used in the fields of navigation, chemical industry, metallurgy, medical treatment, instrumentation, etc. Brazing is a common manufacturing method for titanium alloy parts and structures. The brazing fillers used are silver-based brazing fillers, aluminum-based brazing fillers and titanium-based brazing fillers. Among them, the titanium-based brazing filler has the best performance. Brazing titanium alloys with titanium-based brazing fillers can obtain higher joint strength, even reaching or approaching the strength of the parent material, with excellent corrosion resistance and good oxidation resistance, and the operating temperature can reach 600℃. In the aviation manufacturing industry, it is often used for welding titanium alloy parts such as various pipelines, compressor blades, guide vanes, etc.

[0003] The main alloying elements of commonly used titanium-based solders are Cu, Ni, Zr, Be, V, and Pd. These elements form a low-melting-point eutectic phase with Ti, so the solder alloy has a low melting point and good fluidity. For example, the solidus and liquidus temperature of B-Ti43ZrNiBe (alloy composition is 43wt.% Zr, 12wt.% Ni and 2wt.% Be) is 800-815°C. In order to make the solder have a low melting point and good fluidity, its composition must be uniform. Some titanium-based solder powders prepared by mechanical mixing of titanium powder (or titanium hydrogen powder) and alloy element powder (or pre-alloyed powder) have uneven composition and poor fluidity. They are only suitable for occasions where solder is pre-placed in the brazing seam, and the brazing quality is difficult to guarantee. In order to obtain brazing products with stable quality, a solder with uniform composition should be used.

[0004] For the preparation of titanium-based brazing powder, the biggest difficulty is that titanium reacts with crucible materials and ladle materials, resulting in serious pollution. Therefore, the crucibles and ladle made of magnesium oxide, aluminum oxide or graphite clay used in the gas atomization process of steel cannot be used in the smelting and powder making process of titanium alloy. In order to ensure the purity of the material, the smelting of titanium alloy generally adopts water-cooled copper crucible arc smelting, and the powder making methods include gas atomization method, plasma heating rotating electrode method, centrifugal atomization method, etc. These methods all require large, complex and expensive special equipment. In the titanium alloy gas atomization method, the master alloy rod must be heated by an induction coil to form droplets, and the droplets are atomized and cooled into powder with argon gas. In order to obtain a powder alloy with uniform composition, the master alloy is preferably smelted; that is, a series of processes such as sponge titanium and alloy powder batching, pressing, welding, vacuum consumable electrode smelting, machining, rolling, machining, etc. are processed into master alloy alloy rods. However, the process is complicated and the cost is high. The large amount of argon gas that must be used in the atomization process further increases the production cost of the powder. The plasma heating rotating electrode method and the centrifugal atomization method also require prefabricated master alloy rods, and their equipment is more complex and expensive; the centrifugal atomization method is very technically difficult and not yet mature. At the same time, these methods also have the problem of low fine powder recovery rate. In addition, the titanium-based brazing filler metal required for the current titanium alloy brazing process is usually in small batches (less than 5kg), and the amount of titanium-based brazing filler metal powder used in experiments may be tens of grams. The above three methods are applied to the preparation of such small batches of titanium alloy powder, and their cost is relatively high, resulting in very high powder prices. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing titanium-based solder alloy powder, which is used for low-cost preparation of high-purity titanium-based solder alloy powder.

[0006] The novel titanium-based solder powder preparation method provided by the present invention comprises powder mixing→pressing→microwave sintering under an inert protective atmosphere→hydrogenation→crushing→screening, wherein powders of titanium, zirconium, copper, nickel and the like (or hydrogenated powders, or pre-alloyed powders) and magnesium powder are mixed, pressed, and then heated and sintered in a microwave sintering furnace under the protection of an inert gas; the sintered product is then hydrogenated to make it brittle; and then it is crushed by a ball milling method; the obtained powder is screened to obtain the desired finer titanium-based solder powder.

[0007] The purpose of adding magnesium powder to the mixed powder is: under the protective atmosphere and during the microwave heating process, a magnesium melt is formed in the billet, and alloy elements such as titanium, zirconium, copper, and nickel are dissolved by the magnesium liquid, diffused into it, and homogenized. If the temperature of the billet remains unchanged, the dissolution of the alloy elements will cause the magnesium melt to solidify. Therefore, the temperature should be gradually increased to maintain the existence of the liquid phase. Although a liquid phase is formed, this method is a liquid phase sintering process rather than a smelting process, and there is no crucible material to contaminate the alloy. Providing a positive pressure protective gas can inhibit the evaporation of magnesium.

[0008] The reason for using microwave sintering is that the characteristic of microwave heating is overall heating; when the powder pressed blank is heated in the microwave sintering furnace, the entire blank (core and edge) is quickly raised to the required temperature at the same time, and the heating speed is fast and the temperature inside the blank is uniform. In the traditional radiation heating process, the temperature outside the blank is higher than the core, and the faster the heating speed, the greater the temperature difference between the inside and outside, which will lead to the evaporation of magnesium at the edge of the blank and the uneven composition of the sintered product. After sintering is completed, vacuum is drawn. Due to the high vapor pressure of magnesium, magnesium will escape from the alloy powder to form a porous titanium alloy material.

[0009] When porous titanium alloy is heated in hydrogen, it is easily hydrogenated and becomes a very brittle material, which is easier to be crushed in the subsequent ball milling process.

[0010] The advantages of the titanium-based solder alloy powder preparation method provided by the present invention are: no large-scale special atomization equipment is required, the process is short, and the production cost is much lower than the traditional atomization method. High-purity titanium-based solder powder can be obtained by using high-quality raw material powder and high-purity protective gas. DETAILED DESCRIPTION

[0011] The method for preparing titanium-based solder alloy powder provided by the present invention has the following specific steps and key process parameters:

[0012] (I) Mixed powder

[0013] a. Prepare the raw material powder according to the grade of titanium-based brazing material to be prepared. The raw material powder is composed of Ti powder (or titanium hydrogen powder), Cu powder, Ni powder, Zr powder (or zirconium hydrogen powder), Be powder, V powder or pre-alloyed powders of these elements, and magnesium powder. The content of magnesium powder is 10-50wt.%, and the rest is raw material powder other than magnesium powder; the oxygen content of the raw material powder is ≤0.15%, the nitrogen content is ≤0.03%, the carbon content is ≤0.02%, and the powder particle size is 200-500 mesh.

[0014] b. Mix the raw material powder in a planetary ball mill under argon protection without adding balls, with a ball mill speed of 30-350r / min and a mixing time of 0.5-1h to obtain a mixed material. The purity of the argon gas is ≥99.99%.

[0015] (II) Suppression

[0016] The mixed material is pressed into a columnar blank with a diameter of 10 to 100 mm using a hydraulic press, and the relative density is ≥50%.

[0017] (III) Sintering

[0018] The blank is heated in a microwave sintering furnace under an inert protective atmosphere, first heated from room temperature to 600-650°C at a heating rate of 30-100°C / min; then heated to 800-1000°C at a heating rate of 1-10°C / min; then kept warm for 15-60 minutes; the pressure of the inert protective atmosphere is 1-10 bar; after sintering, vacuum is evacuated, and then cooled with the furnace to obtain a solder alloy.

[0019] (IV) Hydrogenation

[0020] The solder alloy is placed in a hydrogen furnace and heated in a pure hydrogen (purity ≥ 99.99%) atmosphere at a heating temperature of 400-790° C., a hydrogen pressure of 0.007-0.02 MPa, and a heating time of 2-4 hours.

[0021] (V) Crushing

[0022] Under the protection of argon (argon purity ≥ 99.99%), the solder alloy is crushed in a ball mill with a ball-to-material ratio of 1:1 to 2:1, a ball mill speed of 60 to 800 r / min, and a ball milling time of 2 to 5 hours.

[0023] (VI) Screening

[0024] The solder powder with a particle size of 500 to 200 meshes is obtained by sieving with a stainless steel mesh screen.

[0025] The planetary ball mill used in the following examples was purchased from Nanjing Nanda Instrument Co., Ltd., model QM-2SP12. The microwave sintering furnace was purchased from Changsha Longtai Technology Co., Ltd., model MW-L0316V.

[0026] Example 1

[0027] The specific steps for preparing titanium-based brazing filler metal with the grade of B-Ti70CuNi are as follows:

[0028] (1) Prepare raw material powder according to the grade of titanium-based solder to be prepared, with the proportion (weight ratio) being: 70% Ti, 15% Cu, and 15% Ni. The raw material powders are pure titanium powder (produced by Panzhihua Iron and Steel Research Institute), copper powder, and nickel powder (Beijing Xingrongyuan Technology Co., Ltd.). The oxygen content of the titanium powder is 0.15%, the nitrogen content is 0.03%, the carbon content is 0.02%, and the powder particle size is 250-500 mesh; the oxygen content of the copper powder is 0.10%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 325-500 mesh; the purity of the nickel powder is 0.15%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 325-500 mesh. The total weight of the above solder raw material powders is 250g. Mix it evenly with 100g of magnesium powder. The oxygen content of the magnesium powder is 0.05%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 200-325 meshes.

[0029] (2) mixing the raw material powder prepared in step (1) in an inert atmosphere (argon with a purity of ≥99.99%) in a planetary ball mill (without adding balls) at a mixing speed of 200 r / min and a mixing time of 0.5 h to obtain a mixed material;

[0030] (3) Use a hydraulic press to press it into a columnar blank with a diameter of 50 mm and a height of 64 mm, with a relative density of about 60%.

[0031] (4) Heat the blank in a microwave sintering furnace. Heat from room temperature to 650°C at a heating rate of 100°C / min; then heat to 900°C at a heating rate of 10°C / min; keep at 900°C for 15 minutes. The protective gas is argon; maintain positive pressure at 4 bar in the furnace. After sintering, evacuate and cool in the furnace.

[0032] (5) Place the solder alloy in a hydrogen furnace and heat it in pure hydrogen (purity ≥ 99.99%) at a temperature of 650°C, a hydrogen pressure of 0.01 MPa, and a heating time of 2 hours.

[0033] (6) The solder alloy is crushed in a planetary ball mill. The ball-to-material ratio is 1:1. The speed is 200 r / min. The ball milling time is 2 h. The argon gas protection is used; the purity of the argon gas is ≥ 99.99%.

[0034] (7) Sieve with a stainless steel mesh to obtain solder powder with a particle size of 500 to 200 mesh.

[0035] The titanium-based solder alloy powder prepared by the method provided in this embodiment has an irregular block-shaped powder morphology. 230 g of fine powder below 250 mesh was obtained, with a yield of 92%.

[0036] Example 2

[0037] The titanium-based brazing filler metal having a composition of Ti-37.5Zr-15Cu-10Ni is prepared by the following specific steps:

[0038] (1) Prepare the raw material powder according to the grade of titanium-based brazing material to be prepared, with the proportion (by weight) being: 37.5% Zr, 15% Cu, 10% Ni, and the balance being Ti. The raw material powders are pure titanium powder (produced by Panzhihua Iron and Steel Research Institute), copper powder and nickel powder (produced by Beijing Xingrongyuan Technology Co., Ltd.), and zirconium powder (produced by Zhuzhou Runfeng New Materials Co., Ltd.). The oxygen content of the titanium powder is 0.15%, the nitrogen content is 0.03%, the carbon content is 0.02%, and the powder particle size is 250-500 mesh; the oxygen content of the copper powder is 0.10%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 325-500 mesh; the oxygen content of the nickel powder is 0.15%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 325-500 mesh; the oxygen content of the zirconium powder is 0.04%, the nitrogen content is less than 0.006%, the carbon content is less than 0.01%, and the powder particle size is 200-350 mesh. The total weight of the above powders is 500g. Mix it evenly with 150g of magnesium powder. The oxygen content of the magnesium powder is 0.05%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 200-325 mesh;

[0039] (2) mixing the raw material powder prepared in step (1) in an inert atmosphere (argon with a purity of ≥99.99%) in a planetary ball mill (without adding balls) at a mixing speed of 150 r / min and a mixing time of 1 h to obtain a mixed material;

[0040] (3) Use a hydraulic press to press it into a columnar blank with a diameter of 60 mm and a height of about 102 mm. The relative density is about 55%.

[0041] (4) Heat the blank in a microwave sintering furnace. Heat from room temperature to 620°C at a heating rate of 50°C / min. Then heat to 800°C at a heating rate of 2°C / min. Keep at 800°C for 30 minutes. The protective gas is argon; maintain positive pressure, and the pressure in the furnace is 5 bar. After sintering, evacuate and cool in the furnace.

[0042] (5) Place the solder alloy in a hydrogen furnace and heat it in pure hydrogen (purity ≥ 99.99%) at a temperature of 750°C, a hydrogen pressure of 0.02 MPa, and a heating time of 3 hours.

[0043] (6) The solder alloy is crushed in a planetary ball mill. The ball-to-material ratio is 1.5:1. The rotation speed is 150 r / min. The ball milling time is 4 h. The argon gas protection is used; the purity of the argon gas is ≥99.99%.

[0044] (7) Sieve with a stainless steel mesh to obtain solder powder with a particle size of 500 to 200 mesh.

[0045] The titanium-based solder alloy powder prepared by the method provided by the patent has an irregular block powder morphology. 440g of fine powder below 250 mesh is obtained, and the yield is 88%.

[0046] Example 3

[0047] The titanium-based brazing filler metal having a composition of Ti-35Zr-15Cu-15Ni is prepared by the following specific steps:

[0048] (1) Prepare the raw material powder according to the grade of titanium-based brazing material to be prepared, with the proportion (by weight) being: 35% Zr, 15% Cu, 15% Ni, and the balance being Ti. The raw material powders are pure titanium powder (produced by Panzhihua Iron and Steel Research Institute), copper powder and nickel powder (produced by Beijing Xingrongyuan Technology Co., Ltd.), and zirconium powder (produced by Zhuzhou Runfeng New Materials Co., Ltd.). The oxygen content of the titanium powder is 0.15%, the nitrogen content is 0.03%, the carbon content is 0.02%, and the powder particle size is 250-500 mesh; the oxygen content of the copper powder is 0.10%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 325-500 mesh; the oxygen content of the nickel powder is 0.15%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 325-500 mesh; the oxygen content of the zirconium powder is 0.04%, the nitrogen content is less than 0.006%, the carbon content is less than 0.01%, and the powder particle size is 200-350 mesh. The total weight of the above powders is 300g. Mix it with 120g of magnesium powder. The oxygen content of the magnesium powder is 0.05%, the nitrogen content is less than 0.01%, the carbon content is less than 0.01%, and the powder particle size is 200-325 mesh.

[0049] (2) mixing the raw material powder prepared in step (1) in an inert atmosphere (argon with a purity of ≥99.99%) in a planetary ball mill (without adding balls) at a mixing speed of 250 r / min and a mixing time of 1 h to obtain a mixed material;

[0050] (3) Use a hydraulic press to press it into a columnar blank with a diameter of 50 mm and a height of about 71 mm. The relative density is about 58%.

[0051] (4) Heat the blank in a microwave sintering furnace. Heat from room temperature to 635°C at a heating rate of 60°C / min. Heat to 800°C at a heating rate of 4°C / min. Keep at 800°C for 50 minutes. The protective gas is argon; maintain positive pressure at 3 bar in the furnace. After sintering, evacuate the blank and cool it in the furnace.

[0052] (5) Place the solder alloy in a hydrogen furnace and heat it in pure hydrogen (purity ≥ 99.99%) at a temperature of 760°C, a hydrogen pressure of 0.015 MPa, and a heating time of 2 hours.

[0053] (6) The solder alloy is crushed in a planetary ball mill. The ball-to-material ratio is 2:1. The rotation speed is 400 r / min. The ball milling time is 2 h. The argon gas protection is used; the purity of the argon gas is ≥ 99.99%.

[0054] (7) Sieve with a stainless steel mesh to obtain solder powder with a particle size of 500 to 200 mesh.

[0055] The titanium-based solder alloy powder prepared by the method provided by the present invention has an irregular block-shaped powder morphology. 272 ​​g of fine powder below 250 meshes is obtained, and the yield is about 90%.

[0056] The impurity element content of the solder powder was tested using a hydrogen and oxygen analyzer and a sulfur analyzer. It can be seen that the impurity element content of the powder is low, and there is not much increase in the impurity element content compared to the raw materials. This shows that the preparation process has better prevented air and environmental pollution.

[0057] The melting temperatures of the solder powders in the above three embodiments were tested by DSC method. The results are shown in Table 1. It is reported that the melting temperature of the commercial solder with the same composition as that of embodiment 1 is 900-960°C; the melting temperature of the commercial solder with the same composition as that of embodiment 2 is 825-840°C; the melting temperature of the commercial solder with the same composition as that of embodiment 3 is 830-850°C. It can be seen that the solder prepared by the method of the present invention has a melting temperature close to that of the commercial solder and has better brazing process performance.

[0058] In a vacuum brazing furnace, the above three solders were used to test weld TA18 titanium alloy tubes. The tube wall thickness was 1mm and the sleeve length was 5mm. The air tightness and shear strength of the pipe joints were tested. The results showed that under a pressure of 0.65Mpa, the welds did not leak; when the joints were stretched, they all broke in the parent material. This shows that the brazing performance of the solder is good.

[0059] Table 1 Properties of several titanium-based solders prepared by the methods of Examples 1-3 of the present invention

[0060]

[0061] The method proposed in the present invention is used to prepare titanium-based solder, which has a simple process and a short flow. Only small equipment is needed to prepare small batches of titanium-based solder powder, and the powder yield is high. The prepared titanium-based solder has excellent performance.

[0062] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing titanium-based brazing alloy powder, characterized in that: The steps include: (I) Mixed powder a. According to the grade of titanium-based solder to be prepared, raw material powder is prepared; the raw material powder is composed of Ti powder or titanium hydrogen powder, Cu powder, Ni powder, Zr powder or zirconium hydrogen powder, Be powder, V powder, or pre-alloyed powders between the above metal elements, and magnesium powder; wherein the content of magnesium powder is 10 to 50wt.%, and the rest is raw material powder other than magnesium powder; b. Mix the raw material powders in a ball mill under argon protection to obtain a mixture; wherein, during the mixing process, the speed of the ball mill is 30 to 350 r / min, and the mixing time is 0.5 to 1 h; (II) Suppression Pressing the mixture into a columnar blank with a diameter of 10 to 100 mm; (III) Sintering The blank is heated in a microwave sintering furnace under an inert protective atmosphere, firstly heated from room temperature to 600-650°C at a heating rate of 30-100°C / min; then heated to 800-1000°C at a heating rate of 1-10°C / min; then kept warm for 15-60 minutes; the pressure of the inert protective atmosphere is 1-10 bar; after sintering, vacuum is drawn, and then cooled with the furnace to obtain a solder alloy; (IV) Hydrogenation The solder alloy is placed in a hydrogen furnace and heated in a hydrogen atmosphere at a temperature of 400 to 790°C, a hydrogen pressure of 0.007 to 0.02 MPa, and a heating time of 2 to 4 hours; (V) Crushing Under argon protection, the solder alloy is crushed using a ball mill, the speed of the ball mill is 60-800 r / min, and the ball milling time is 2-5 h; (VI) Screening The solder alloy is screened by a mesh screen to obtain solder powder with a particle size of 500 mesh to 200 mesh; The oxygen content of the raw material powder is ≤0.15%, the nitrogen content is ≤0.03%, and the carbon content is ≤0.02%; and the particle size of the raw material powder is 200-500 meshes.

2. The method according to claim 1, characterized in that The purity of the argon gas is ≥99.99%, and the purity of the hydrogen gas is ≥99.99%.

3. The method according to claim 1, characterized in that: In step (a), no balls are added during the powder mixing process.

4. The method according to claim 1, characterized in that The relative density of the columnar blank is ≥50%.

5. The method according to claim 1, characterized in that: In step (five), the ball-to-material ratio is 1:1 to 2:1.

Citation Information

Patent Citations

  • Brazing and casting process of metal ceramic composite lining board

    CN102554385A

  • Preparation method of 3D printing medical titanium alloy powder material

    CN110524000A

  • Sintering method for titanium or titanium alloy powder

    CN111375758A

  • Powdery titanium-based brazing filler metal and preparation method thereof

    CN114226735A